Targeting senescent microglia in progressive multiple sclerosis: a geroscience-informed approach - Atkinson, Jeffrey; Dokiburra, Amy; Groover, Hayley; Godbout, Jonathan P.; Segal, Benjamin M.; Zhang, Yinan (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative disorder of the central nervous system (CNS). Age is the strongest predictor of disease phenotype, with the majority of older adults transitioning to a progressive form marked by irreversible neurological decline. This clinical progression is associated with smoldering, CNS-compartmentalized inflammation and neurodegeneration, for which there are currently no effective disease-modifying therapies. Cellular senescence, characterized by the secretion of pro-inflammatory mediators collectively known as the senescence-associated secretory phenotype (SASP), increases with age and contributes to tissue injury. In MS, neuroinflammation can further promote cellular senescence, creating a self-reinforcing cycle of damage. Senescent microglia have been identified within MS lesions, where their SASP may impair remyelination and exacerbate neurodegeneration. Senolytic agents selectively target and eliminate senescent cells by disrupting anti-apoptotic pathways. In experimental autoimmune encephalomyelitis (EAE), a widely used model of MS, senolytic treatment reduces senescent microglia burden and attenuates disease severity in an age- and drug-dependent manner. Specifically, here we show that middle-aged mice (40–44 weeks) with EAE exhibit improved clinical outcomes and survival following treatment with either dasatinib plus quercetin (D+Q) or navitoclax. Early-phase clinical trials of senolytics in age-related diseases have demonstrated functional benefits, including improved gait speed in idiopathic pulmonary fibrosis and CNS penetrance in Alzheimer’s disease. Translating senolytic therapy to MS will require careful selection of CNS-penetrant and well-tolerated agents, identification of appropriate patient populations, and deployment of responsive biomarkers. Senolytic therapy represents a promising geroscience-based strategy to meet the urgent therapeutic need in progressive MS.